2016
DOI: 10.1093/mnras/stw1775
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the nature of the Lyman-α emitter CR7

Abstract: CR7 is the brightest Lyman-α emitter observed at z > 6, which shows very strong Lyman-α and Heii 1640Å line luminosities, but no metal line emission. Previous studies suggest that CR7 hosts either young primordial stars with a total stellar mass of ∼ 10 7 M ⊙ or a black hole of 10 6 M ⊙ . Here, we explore different formation scenarios for CR7 with a semianalytical model, based on the random sampling of dark matter merger trees. We are unable to reproduce the observational constraints with a primordial stellar … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 180 publications
(251 reference statements)
3
65
0
Order By: Relevance
“…For this, we shift the functional form of the H17 OF by 1 dex in stellar mass, and modify the plateau at low mass with a linear extrapolation, down to OF=0 ("H17low1") or OF=0.01 ("H17low2"). We have compared the shifted scaling to the occupation fraction in two studies that model DCBHs, the simulation of Tremmel et al (2017), and the semi-analytical model by Hartwig et al (2016). Occupation fractions are unpublished, but the authors provided us with their values, and the results are similar to the rescaled/shifted valued we estimated.…”
Section: Luminosity Functions and Dependence On "Seed" Bh Propertiesmentioning
confidence: 77%
“…For this, we shift the functional form of the H17 OF by 1 dex in stellar mass, and modify the plateau at low mass with a linear extrapolation, down to OF=0 ("H17low1") or OF=0.01 ("H17low2"). We have compared the shifted scaling to the occupation fraction in two studies that model DCBHs, the simulation of Tremmel et al (2017), and the semi-analytical model by Hartwig et al (2016). Occupation fractions are unpublished, but the authors provided us with their values, and the results are similar to the rescaled/shifted valued we estimated.…”
Section: Luminosity Functions and Dependence On "Seed" Bh Propertiesmentioning
confidence: 77%
“…Recent modeling efforts have demonstrated that a nearby galaxy may well have produced a high enough level of LW radiation to induce the formation of a DCBH in this galaxy and that the nebular emission could be explained by an accreting BH with a mass consistent with formation as a DCBH (e.g. Pallottini et al 2015;Agarwal et al 2016c;Hartwig et al 2016;Smidt et al 2016;Smith et al 2016;Dijkstra et al 2016a). 3 In suggesting that the critical LW flux may be lower than previously thought, our results lend support to DCBH scenario for the origin of CR7.…”
Section: Discussionmentioning
confidence: 99%
“…Sobral et al 2015;Visbal et al 2016; see also Johnson 2010), is dubious since it is unknown how a sufficiently high mass of Population III stars could be assembled rapidly enough to explain the observed extremely bright emission (e.g. Hartwig et al 2016;Yajima & Khochfar 2016;Xu et al 2016;Visbal et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Since the first detection of GW150914, several investigations have examined how double black hole binaries could have been produced from the evolution of massive stars, whether from classical isolated evolution in low-metallicity environments (Belczynski et al 2016a;Eldridge & Stanway 2016); via the aid of rapid rotation and hence homogeneous chemical evolution Woosley 2016); via Population III stars (Hartwig et al 2016;Inayoshi et al 2016;Dvorkin et al 2016); or from dynamical formation in interacting environments (Mapelli 2016;Rodriguez et al 2016). Other more exotic scenarios have been introduced and discussed in the context of GW150914; dark matter primordial BH-BH formation (Sasaki et al 2016;Eroshenko 2016), formation of a BH-BH merger from a divided core of a massive rapidly rotating single star (Loeb 2016), or formation of BH-BH mergers with disks around BHs formed from fallback material in weak supernova explosions (Perna et al 2016).…”
Section: Introductionmentioning
confidence: 99%